Hubungan Efikasi Diri Dengan Hasil Belajar PPKn Kelas IV SDN Kecamatan Bekasi Timur - Medhitya Alda Apriliani; Nina Nurhasanah; Arifin Maksum (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
Learning activity is closely related to learning outcomes. Learning outcomes can reflect the competencies possessed by students. One of the essential and substantial factors contained in students that can affect the acquisition of learning outcomes is self-efficacy. Self-efficacy makes students have goals, commitment to achieving goals, activities to be carried out, perseverance or effort to be issued, and student achievement in learning activities. This study aims to determine and obtain an overview of the relationship between self-efficacy and learning outcomes of Civics Class IV SDN Bekasi Timur District. In addition, this study aims to determine how much self-efficacy contributes to Civics learning outcomes. This study uses a quantitative approach and is included in bivariate correlation. The research instrument used was a questionnaire with a Likert and multiple-choice objective test. The data analysis technique used the correlation coefficient test with Pearson Product Moment and the correlation coefficient significance test with the t-test. The existence of a relationship or correlation between the self-efficacy variable and the Civics learning outcome variable is indicated by the correlation coefficient value of 0.917 and the correlation coefficient significance value of t-count 31,438 > t-table 1,653, so it can be concluded that there is a positive and significant relationship between the two variables. Then, calculating the coefficient of determination results showed that self-efficacy contributes to Civics learning outcomes by 84.09% and other factors influence the remaining 15.91%. It means self-efficacy is positively and significantly related to Civics learning outcomes for fourth-grade students at SDN Bekasi Timur District in the 2021/2022 academic year. In addition, self-efficacy provides a more significant contribution to the acquisition of Civics learning outcomes than the contribution of other factors